OTT opportunities for public broadcasters: A review and cross-country analysis in European countries - Athanasios Papathanasopoulos; Dimitris Varoutas (International Telecommunications Society (ITS), 2023)
This analysis examines the opportunities and challenges presented by Over-The-Top (OTT) platforms for public service broadcasters in different European countries. Through a cross-country analysis of several EU countries, namely: France, Germany, Greece, Italy, the Netherlands, Romania, and Sweden, this paper provides a comprehensive perspective on the topic. The analysis includes revenue trends, subscriber numbers, and other indicators to evaluate the performance of public broadcaster-owned OTT platforms. The findings suggest that while OTT platforms present challenges for public broadcasters, they also offer opportunities for these broadcasters to compete and attract viewers in a rapidly changing media landscape.
Keywords: 330; OTT platforms; Public Service Broadcasting; media competition